2006
DOI: 10.1242/jeb.01977
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress during stressful heat exposure and recovery in the North Sea eelpoutZoarces viviparusL.

Abstract: SUMMARY The interplay between antioxidants, heat shock proteins and hypoxic signaling is supposed to be important for passive survival of critical temperature stress, e.g. during unfavorable conditions in hot summers. We investigated the effect of mild (18°C), critical (22°C) and severe(26°C) experimental heat stress, assumed to induce different degrees of functional hypoxia, as well as the effect of recovery following heat stress on these parameters in liver samples of the common eelpout Zoarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 59 publications
7
88
1
3
Order By: Relevance
“…We have investigated the HIF response to cold shock in North Sea eelpout (Heise et al 2006a) and found HIF-1 DNA binding in liver tissue (the only organ we investigated) significantly enhanced following 2 h cold exposure to 1 and 5°C, compared to control fish kept at 12°C. In contrast, 2 h of heat shock above 20°C failed to have an effect on eelpout HIF (Heise et al 2006b). Based on these previous findings, we hypothesized that HIF-1 signalling could especially be involved in the physiological regulation supporting seasonal and regional cold tolerance in fish.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have investigated the HIF response to cold shock in North Sea eelpout (Heise et al 2006a) and found HIF-1 DNA binding in liver tissue (the only organ we investigated) significantly enhanced following 2 h cold exposure to 1 and 5°C, compared to control fish kept at 12°C. In contrast, 2 h of heat shock above 20°C failed to have an effect on eelpout HIF (Heise et al 2006b). Based on these previous findings, we hypothesized that HIF-1 signalling could especially be involved in the physiological regulation supporting seasonal and regional cold tolerance in fish.…”
Section: Introductionmentioning
confidence: 91%
“…Calculation of the percentage intensity was based on densitometry of gel images, with the sum of all four bands taken as 100% value. Control experiments for testing the specificity of the human EPO enhancer by adding an excess of unlabeled probe or by adding antibody (against the N-terminus of rainbow trout HIF-1a, see above) are described in our previous study on Z. viviparus (Heise et al 2006b). No antibody was available which recognised the HIF-1a protein in liver samples from P. brachycephalum.…”
Section: Dna-binding Activity Of the Hypoxia Inducible Factor (Hif-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The range of active thermal tolerance (see Glossary) is limited on both sides by pejus temperatures (T p ; the box lists processes supporting active tolerance, which become constrained beyond T p ). Towards warm and cold extremes, the transition to passive thermal tolerance (see Glossary) is indicated by a decline in (venous) P O2 (solid black arrows), causing oxidative stress (Heise et al, 2006), heat shock response and, finally, transition to anaerobic metabolism (e.g. Kyprianou et al, 2010;Pörtner and Knust, 2007;dashed black arrows).…”
Section: Sublethal Limitsmentioning
confidence: 99%
“…due to warming) until reaching different capacity limits (under routine conditions, indicated by breakpoints, BP). Through similar principles and differences in thermal responses (Q 10 ), OCLTT distinguishes stenotherms from eurytherms (here exemplified through narrow versus wide temperature ranges and differences in the temperature dependence of the workloads; see Pörtner, 2006). In each case, the thermal window width of functional scope is represented by the length of the dashed arrows.…”
Section: Variables Indicative Of Oclttmentioning
confidence: 99%